An Improved Nishihara Model for Frozen Loess considering the Influence of Temperature - Xin Li; Enlong Liu; Bingtang Song; Xingyan Liu (Advances in Materials Science and Engineering)
A series of triaxial creep tests under the constant confining pressure are performed on frozen loess specimens, and the creep behavior of the frozen loess with respect to variations in both temperature and deviator stress is examined. Experimental results illustrate that the frozen loess specimens present the attenuation creep at the lower deviatoric stress, whereas the nonattenuation creep under the higher deviatoric stress level, and with a drop in the temperature, the deviator stress value which the exhibition of nonattenuation creep needs will increase under the constant confining pressure condition. According to the microscopic analysis on deformation characteristics in the creep process of frozen soil, both temperature and external stress will cause the hardening and weakening effects, affecting the creep properties of frozen loess. By introducing the hardening variable and damage variable to consider the hardening and weakening effects of the frozen loess, an improved Nishihara model is proposed. The correlations between model parameters and the temperature as well as deviator stress are determined. The comparisons between model predictions and experimental results show that the improved creep constitutive model proposed here can not only describe the whole creep process well, but also reveal the influences of the temperature and deviator stress on the creep behavior of frozen loess, which demonstrate its accuracy and usefulness.